Spanning the Solar Spectrum: Azopolymer Solar Thermal Fuels for Simultaneous UV and Visible Light Storage. Issue 3 (12th October 2016) - Saydjari, Andrew K.; Weis, Philipp; Wu, Si
Abstract : A UV‐sensitive azopolymer and a visible‐light‐sensitive azopolymer are combined with a fluorescent dye and a filter to create a four‐layer solar thermal cell with record efficiency gravimetric energy density. While most azopolymers discharge under visible irradiation, this device can use a true solar spectrum because fluorescent down‐conversion enables storage of light that would otherwise cause discharging.